Ukraine one year later: Impacts on global food security - Glauber, Joseph W. (International Food Policy Research Institute, 2023)
When Russian troops invaded Ukraine one year ago, the war appeared to pose a grave threat to global food security. The conflict could hardly have come at a worse moment. Even prior to the war, global supplies of key staples were tight; ending stocks of wheat, maize, and soybeans were at their lowest levels for many years and prices were high compared to 2020 levels — lingering effects of the COVID-19 pandemic. The outbreak of war between two of the world’s key agricultural producers jeopardized more than a third of world wheat trade, 17% of world maize trade, and almost 75% of world sunflower oil trade. Within a week of the invasion, prices of wheat futures had jumped almost 60%, while corn and soybean prices were up over 15% (Figure 1). Ukraine found its Black Sea ports effectively blockaded, sharply limiting its ability to export its 2021 crops, and the planting and harvest of its 2022 crops disrupted. The world faced the possibility of another food price crisis with potentially devastating consequences, following on the heels of the pandemic’s global economic disruptions.